Replication of the Mammalian Genome by Replisomes Specific for Euchromatin and Heterochromatin - Zhang, Jing; Bellani, Marina A.; Huang, Jing; James, Ryan C.; Pokharel, Durga; Gichimu, Julia; Gali, Himabindu; Stewart, Grant; Seidman, Michael M. (Frontiers in Cell and Developmental Biology, 2021)
Replisomes must navigate the entire genome, following a schedule in which replication of DNA in euchromatin is early in S phase while sequences in heterochromatin replicate late. Impediments to DNA replication, referred to as replication stress, can stall replication forks triggering activation of the ATR kinase and downstream pathways. While there is substantial literature on the local consequences of replisome stalling- double strand breaks, reversed forks, or genomic rearrangements- there is limited understanding of the determinants of replisome stalling vs continued progression. Although many proteins are recruited to stalled replisomes, current models assume a single species of “stressed” replisome, independent of genomic location. Here we describe our approach to visualizing replication fork encounters with the potent block imposed by a DNA interstrand crosslink (ICL) and our discovery of an unexpected pathway of replication restart (traverse) past an intact ICL. Additionally, we found two biochemically distinct replisomes distinguished by activity in different stages of S phase and chromatin environment. Each form contains different proteins that contribute to the traverse of the ICLs.